(untitled) (Raparin Journal of Humanities (RJH), 2026)
The nature and essence of language is such that human beings cannot clearly comprehend, analyze, and interpret it without using it in a practical way. Functional linguistics is one of the subjects and issues of modern linguistics that emphasizes the study of language from a social perspective and the functions that language performs in society. That is to say; the school of functional existence of language connects, on one hand, to the existence of society and, on the other hand, to the functions that language performs or indicates In this regard, the British linguist Michael Halliday has conducted research in this field and has attempted to clarify the role of language relationships as a large system whose parts are interconnected and inseparable from each other. From this point of view, he shows that language serves seven different functions, particularly in early childhood development. These functions reveal how children use language to meet various needs and interact with their environment. This study aims to analyze and explain the fundamental functions of language in the Kurdish language, based on Halliday’s systemic functional linguistic theory. For this purpose, the book "Kurdish Reading" for third grade primary level has been used as a sample.